AKTIVITAS ANTIFUNGI SARI DAUN PEPAYA (Carica papaya L.) TERHADAP Candida albicans - Siska Nuryanti (As-Syifaa Jurnal Farmasi, 2017)
A research had been done on antifungal activity of papaya leaf ekstract (Carica papaya L.) and the aim was to determine the antifungal activity and inhibitory potency. The research was started by screening  test using Candida albicans. Results showed  that the papayaleaf ekstract inhibited Candida albicans. The research was continued by Minimum Inhibitory Concentration (MIC) test by liquid dilution method in Potato Dekstrosa Broth medium toward, Candida albicans in concentration of MIC 5%, 10%, 15% and 20%. Result showed that papaya leaf ekstract (Carica papaya L.) has antifungal activity wich was indicated by the inhibitory zone diameter in concentration of 10%, 15%, and 20% respectively on Candida albicans.